2008
DOI: 10.1177/1756285608095747
|View full text |Cite
|
Sign up to set email alerts
|

Review: New advances in the treatment of neurological diseases using high dose intravenous immunoglobulins

Abstract: Since the incidental discovery in 1981 that intravenous immunoglobulins (IVIg) are immunomodulatory, they have been investigated in a large number of putative autoimmune diseases. This has led to licensing for idiopathic thrombocytopenic purpura, Kawasaki disease, and in neurological disorders for Guillain-Barré syndrome (GBS). Although not licensed, randomized controlled trials have also shown IVIg efficacy in other neuroimmunological diseases such as multifocal motor neuropathy (MMN), chronic inflammatory de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 100 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…Clinical studies have shown efficacy of high dose intravenous IG (IVIG) in Guillain Barré syndrome (GBS), chronic inflammatory demyelinating polyneuropathy (CIDP), or multifocal motoric neuropathy (MMN) and provided the basis for regulatory approval of some preparations in these indications (Elovaara et al 2008;Stangel and Gold 2010). In other neurological AID such as myasthenia gravis, dermatomyositis or stiffperson syndrome efficacy of intravenous IG has been shown in controlled studies, but agents are used as second line, in case of non-response to other immunotherapeutics or intolerability to these drugs (Gold et al 2007;Stangel 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Clinical studies have shown efficacy of high dose intravenous IG (IVIG) in Guillain Barré syndrome (GBS), chronic inflammatory demyelinating polyneuropathy (CIDP), or multifocal motoric neuropathy (MMN) and provided the basis for regulatory approval of some preparations in these indications (Elovaara et al 2008;Stangel and Gold 2010). In other neurological AID such as myasthenia gravis, dermatomyositis or stiffperson syndrome efficacy of intravenous IG has been shown in controlled studies, but agents are used as second line, in case of non-response to other immunotherapeutics or intolerability to these drugs (Gold et al 2007;Stangel 2008).…”
Section: Introductionmentioning
confidence: 98%
“…However, it is not established the advantage of one method instead of the other in cases of recurrence or no response if another course should be given or plasma exchange performed 2, 22 . In MMN, it is established in different randomized controlled trials the first-line treatment function of IVIg, using the same initial dose of GBS, irrespective of the presence of positivity for anti-GM1 ganglioside antibody or conduction block 2, 22 . Refractory cases or partial responses are indicative of the possible use of immunomodulatory drugs.…”
Section: Classical and Current Neurological Indicationsmentioning
confidence: 99%
“…Among all peripheral neuropathy and polyradiculoneuropathy, most studies with promising and positive results with immunoglobulin involved patients with multifocal motor neuropathy (MMN), Guillain-Barré syndrome (GBS) and variants, and CIDP. In CIDP with moderate to severe motor disability, IVIg is proven as the first-line immunotherapy, including for maintenance treatment associated with immunomodulatory drugs 2, 13,22 . In GBS, similarly to the observed effect of plasma exchange therapy, equal responses and effects are observed with IVIg in the standard classical dose of 400 mg/kg per day for 5 days.…”
Section: Classical and Current Neurological Indicationsmentioning
confidence: 99%
See 2 more Smart Citations